2022
DOI: 10.1111/jeb.13998
|View full text |Cite
|
Sign up to set email alerts
|

A variance partitioning perspective of assortative mating: Proximate mechanisms and evolutionary implications

Abstract: Assortative mating occurs when paired individuals of the same population are more similar than expected by chance. This form of non‐random assortment has long been predicted to play a role in many evolutionary processes because assortatively mated individuals are assumed to be genetically similar. However, this assumption may always hold for labile traits, or traits that are measured with error. For such traits, there is a variety of proximate mechanisms that can drive phenotypic resemblance between mated part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
0
4
0
1
Order By: Relevance
“…For example, body size was previously reported as a strong premating barrier in different animal groups 26 28 . In this context, male assortative mating by size has been described in H. americana sensu lato 29 , and even though we cannot ensure interspecific discrimination of females based on their size, it has been widely recognized that assortative mating can promote or reinforce divergence even in incipient species and in the presence of gene flow 30 , 31 . Assortative mating in males of H. americana y H. calverti could have two causes: first, males prefer mates with specific trait values, in this case larger females because they may be more fertile (and not because they discriminate between species).…”
Section: Discussionmentioning
confidence: 96%
“…For example, body size was previously reported as a strong premating barrier in different animal groups 26 28 . In this context, male assortative mating by size has been described in H. americana sensu lato 29 , and even though we cannot ensure interspecific discrimination of females based on their size, it has been widely recognized that assortative mating can promote or reinforce divergence even in incipient species and in the presence of gene flow 30 , 31 . Assortative mating in males of H. americana y H. calverti could have two causes: first, males prefer mates with specific trait values, in this case larger females because they may be more fertile (and not because they discriminate between species).…”
Section: Discussionmentioning
confidence: 96%
“…Thus, the personality pair composition in our study population does not necessarily reflect the situation in the wild. Future studies should examine the variation in pair personality composition in wild common marmosets and the mechanisms underlying it, such as mate choice, social conformity or stratification of personality types in the space or time 67 . Studies on captive fish 68 , birds 69 , and mammals 70 with biparental care have shown that females choose partners based on their personality, and these pairs have higher reproductive success.…”
Section: Discussionmentioning
confidence: 99%
“…Among‐individual differences in nest defense could also be maintained through nonrandom mating, whereby the fitness of particular combinations of parent behavioral types (i.e., individuals mean phenotypic value for a behavioral trait) have higher success because they are behaviorally and/or genetically more compatible (Class & Dingemanse, 2022 ; Jiang et al, 2013 ; Tregenza & Wedell, 2000 ). Positive assortative mating (hereafter referred to as “assortative mating”) based on behavioral type can contribute to the maintenance of among‐individual differences if pairing with individuals of similar phenotype (i.e., high aggression with high aggression, low aggression with low aggression) has a net positive fitness outcome (Jiang et al, 2013 ; Schuett et al, 2010 ; Tregenza & Wedell, 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among-individual differences in nest defense could also be maintained through nonrandom mating, whereby the fitness of particular combinations of parent behavioral types (i.e., individuals mean phenotypic value for a behavioral trait) have higher success because they are behaviorally and/or genetically more compatible (Class & Dingemanse, 2022;Jiang et al, 2013;Tregenza & Wedell, 2000).…”
Section: Introductionmentioning
confidence: 99%